Cascading Reliability Assessment of International Railway Freight Network Based on Coupled Map Lattices: A Case Study of China Railway Express - Si Chen; Xinyi Chi; Qian Zhang; Yinying Tang; Zhen Liu; Wenkai Tan (Journal of Advanced Transportation)
The cascading reliability problem of international railway freight network is becoming noticeable due to the limitation of node transportation capacity with increases in the transport volume of the international railway freight trains. We discuss this problem in this study, thereby focusing on the failure process of the international railway freight network. As the first step, we consider three factors of node degree, node betweenness, and edge betweenness based on the complex network theory, and establish the node model using coupled map lattice method. Next, we select three indicators to evaluate the reliability characteristics of the network and evaluate the robustness of the network with the maximum effective graph and the network efficiency. Finally, we apply the model to the China Railway Express freight network and consider two situations: cascading failures and noncascading failures that are corresponding to two strategies: redistributing cargoes and disbanding cargoes. The results show that the cascading reliability of the China Railway Express freight network is not high. The indicators decrease less than 10% under noncascading failure, while more than 40% under cascading failure, so the network is more reliable under noncascading failure. Our research provides a new way to test the cascading reliability of the international railway freight network and provide different strategies for improving reliability.